Macrophage-CD4+ T cell interactions in HIV-1 spread - Duncan, C; Christopher Duncan (2013)
Macrophages and CD4+ T cells are the main targets for productive human immunodeficiency virus-1 (HIV-1) infection in vivo. HIV-1 transmission at immune cell synapses, such as the multi-molecular HIV-1-induced virological synapse (VS) formed between T cells, is a more efficient method of viral dissemination than infection by cell-free virus, with important implications for HIV-1 prophylaxis and eradication. Infected macrophages can transfer HIV-1 to CD4+ T cells in a contact- dependent manner. However, the mechanism(s) of intercellular HIV-1 transmission between primary macrophages and CD4+ T cells are poorly defined. Here I investigate the organisation of the macrophage-T cell VS, which like the VS formed between T cells is dependent on envelope glycoprotein (Env) binding to CD4, and is stabilised by ICAM-1/LFA-1 interactions. However, unlike the T cell VS, where polarised budding of virions occurs at the donor cell membrane, VS-transmission from macrophages involves actin-dependent relocation of HIV-1 contained within the macrophage virus-containing compartment. Macrophage VS-mediated transmission results in highly efficient productive T cell infection at multiplicities capable of largely overcoming antiretroviral inhibition. Compared with cell-free infection of T cells, VS-transmission by macrophages is equally susceptible to broadly neutralising antibodies (bNAbs) against gp120, but relatively resistant to bNAbs targeting the membrane-proximal external region of gp41, probably via steric hindrance. In a related project, I investigated how HIV-1-infected CD4+ T cells might infect macrophages. Interaction of macrophages with HIV-1-infected CD4+ T cells resulted in rapid phagocytic uptake of the infected T cells, which correlated with efficient productive macrophage infection. This route of transmission also permitted macrophage infection with transmitted/founder HIV-1 clones that inefficiently replicate in macrophages following cell-free inoculation, potentially implicating macrophages in the mucosal amplification of transmitted HIV-1. Overall, these data indicate an important role for cell-to-cell transmission between macrophages and CD4+ T cells in various aspects of HIV-1 pathogenesis.